2009
DOI: 10.1017/s1368980008003248
|View full text |Cite
|
Sign up to set email alerts
|

Meals and snacks from the child’s perspective: the contribution of qualitative methods to the development of dietary interventions

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 39 publications
0
27
0
2
Order By: Relevance
“…Across studies, children were able to list positive short term outcome expectancies of eating fruit and vegetables: General health, growth (give you strength, make you stronger, help the body grow and make you taller, more muscular), nutritious and hunger satisfaction (contain vitamins, specific nutrients, good for the eyes and teeth, make you feel full after eating it), cosmetics benefits (looking good, improved body image, improved skin appearance, avoid fatness, remain slender, loose or gain weight, pretty teeth), improve performance and productivity in school work and sports/athletics (fuel for the brain, give energy, refreshing and reviving effect as opposed to unhealthy food that slows down the mind and body), sensory aspects (taste, sweetness, crunchiness, fun to eat) [25,27,29,31-34,36-39,41,42,45,51,52]. Negative short term expectancies of eating fruit and vegetables were explicitly discussed in one US study: Make you go to the loo, gas in your stomach, get stuck in your teeth, allergy [29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Across studies, children were able to list positive short term outcome expectancies of eating fruit and vegetables: General health, growth (give you strength, make you stronger, help the body grow and make you taller, more muscular), nutritious and hunger satisfaction (contain vitamins, specific nutrients, good for the eyes and teeth, make you feel full after eating it), cosmetics benefits (looking good, improved body image, improved skin appearance, avoid fatness, remain slender, loose or gain weight, pretty teeth), improve performance and productivity in school work and sports/athletics (fuel for the brain, give energy, refreshing and reviving effect as opposed to unhealthy food that slows down the mind and body), sensory aspects (taste, sweetness, crunchiness, fun to eat) [25,27,29,31-34,36-39,41,42,45,51,52]. Negative short term expectancies of eating fruit and vegetables were explicitly discussed in one US study: Make you go to the loo, gas in your stomach, get stuck in your teeth, allergy [29].…”
Section: Resultsmentioning
confidence: 99%
“…Wind et al (2005) found that 11-year-olds from the Netherlands were allowed to and liked to prepare fruit and vegetable dishes whereas 11-year-olds from Belgium-Flanders often were not allowed to cut up vegetables themselves or to be involved in preparing the dinner, but that they were allowed to prepare fruit [38]. Similarly some Danish 11-year-olds were not allowed to use sharp knives which prevented them from having pineapples for example if their parents did not cut them up for them [51]. According to Kubik et al (2005), cooking classes to learn about healthy eating and how to cook cheap food were popular among students in secondary school [54].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be related to a positive family food environment, as reported by Hang et al 22 Parents limit access to unhealthy snacks, and this barrier could be diminished in families where mothers are not employed, because of the high level of disadvantages among this group. [23][24][25] Children of full-time employed mothers were also less likely to regularly eat dinner. It is possible that time could be delayed for children of full-time employed mothers.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, os filhos de pais mais permissivos tendem a ter hábitos alimentares menos saudáveis 27 . Diante dos diferentes enfoques dados ao modo como os pais devem agir para auxiliar na formação dos hábitos alimentares de seus filhos, observa-se que os melhores resultados são obtidos quando os hábitos e o ambiente familiar servem de base para as práticas alimentares das crianças 28 .…”
Section: I S C U S S ã Ounclassified